Application of “parenchyma-first” approach in laparoscopic living donor left lateral sectionectomy - Hui Tang; Dongwei Wu; Kaining Zeng; Xiao Feng; Binsheng Fu; Qing Yang; Jia Yao; Yang Yang; Shuhong Yi (Frontiers in Surgery, 2026)
Objective This study aimed to evaluate the safety and feasibility of a “Parenchyma-First” approach for laparoscopic left lateral sectionectomy (LLS) in living donor hepatectomy, with the primary goal of minimizing vascular injury. Methods To avoid premature and excessive dissection of the portal vein and hepatic artery at the first hepatic hilum—which increases the risk of vascular injury—and to prevent torsion or occlusion of these mobilized vessels during parenchymal transection, we adopted a technique that prioritizes liver parenchymal transection before dissecting the left hepatic artery and left portal vein branch. A single-center, retrospective, descriptive study of 46 donors and pediatric recipients (April 2023–June 2025). No control group was included. Results Mean donor operative time was 289.7 ± 66.7 min, blood loss 71.5 ± 60.3 mL, and warm ischemia time 297.8 ± 98.6 s. No donor vascular or biliary complications occurred; one donor underwent reoperation for omental bleeding. Among recipients, mortality was 4.3% (2/46) due to recipient-related vascular complications. Vascular or biliary interventions were required in 10.9% (5/46) of recipients. Early allograft dysfunction occurred in 17.4% of recipients. Conclusion The “Parenchyma-First” approach for left lateral section graft procurement is technically feasible, provides excellent donor safety by protecting hilar vasculature, and yields acceptable recipient outcomes comparable with international series.